Anion-cation-doped carbon-coated positive electrode material and preparation method thereof, sodium-ion battery and electric equipment
By introducing Mn2+, Ni2+ cations and (SiO4F)5-anions into the carbon-coated sodium iron phosphate positive electrode material, the problem of narrowing of Na+ diffusion channel during the charging process is solved, the electron conductivity, ionic conductivity and structural stability are improved, and the electrochemical performance is enhanced.
Patent Information
- Application Number
- CN202411941865.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
During the charging process, the diffusion channel of Na+ of sodium ferric phosphate positive electrode material becomes narrower, affecting structural stability, and has low electronic conductivity and ionic conductivity, which limits its electrochemical performance.
Mn2+, Ni2+ cations and (SiO4F)5-anions are introduced into the carbon-coated sodium iron phosphate positive electrode material. Through doping and the design of the carbon-coated layer, the electronic conductivity, ionic conductivity and structural stability of the material are improved.
The electronic conductivity, ionic conductivity and structural stability of the sodium ferric phosphate pyrophosphate positive electrode material are improved, and its electrochemical properties are enhanced.
Smart Images

Figure CN119725478A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an anion-cation inter-doped carbon-coated positive electrode material and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art
[0002] Due to the increasingly urgent demand for energy, the sustainable storage of new energy in large-scale energy storage systems has become a key issue that needs to be solved worldwide. As a promising stationary energy storage technology, sodium-ion batteries have the advantages of good low-temperature performance, low cost, and abundant materials compared with lithium-ion batteries. At present, sodium-ion cathode materials with commercial application prospects include layered oxides, polyanions, and Prussian blue. Among them, the structural phase change of layered oxides brings many unstable factors to the deintercalation of sodium ions, and the introduction of expensive Ni and Cu elements to improve performance is costly, which is not conducive to large-scale application in the future market; Prussian blue materials have a large number of Fe(CN)6 defects and crystal water in the structure, which leads to structural failure and gas production when sodium ions are deintercalated, making commercial application difficult; while polyanion compounds have a rigid open framework and can stably store sodium ions. In terms of resource cost, the abundance of Fe in the earth's crust is 5.00%, which is much higher than Mn, V, and Co. Iron-based polyanion compounds have cost-effectiveness and environmental friendliness.
[0003] Iron-based materials have become a highly commercially valuable cathode material system for sodium-ion batteries due to their easy availability and wide range of sources. Among them, sodium iron pyrophosphate has a simple preparation method and good cycle performance, and has gradually become the preferred cathode material for sodium-ion battery energy storage systems. However, during the charging process of sodium iron pyrophosphate, as the sodium is removed, the distortion of the Fe-O octahedron and the PO bond will cause Na + The diffusion channel of Na + The migration rate of sodium ferric pyrophosphate is reduced; on the other hand, the larger polyanion group (PO4) in sodium ferric pyrophosphate 3- It will interact with the surrounding electrons, causing the electrons to gather locally in the crystal and not be easily transmitted freely throughout the crystal, thus reducing the conductivity of the positive electrode material. Therefore, it is necessary to develop a sodium iron pyrophosphate positive electrode material with stable performance. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, embodiments of the present invention provide an anion-cation inter-doped carbon-coated positive electrode material and a preparation method thereof, a sodium ion battery and an electrical device.
[0006] In the first aspect, the present invention provides a carbon-coated positive electrode material doped with anions and cations, wherein the positive electrode material is Na 4+2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z and C composite material, wherein 0<x≤0.5, 0<y≤0.5, 0<z≤0.3, and the mass proportion of C in the positive electrode material is 1% to 3%.
[0007] In a second aspect, the present invention provides a method for preparing the anion-cation inter-doped carbon-coated positive electrode material provided in the first aspect, comprising the following steps:
[0008] (a) weighing a sodium source, an iron source, a manganese source, and a nickel source in molar ratio, dissolving them in water, adding a surfactant and a chelating agent, and stirring and mixing them to obtain a metal ion complex solution;
[0009] (b) weighing a carbon source, a phosphorus source, a silicon source, and a fluorine source in molar ratio and dissolving them in water, adding the metal ion complex solution, and stirring and mixing to obtain a mixed solution;
[0010] (c) heating the mixed solution to a high temperature, adding an auxiliary agent dropwise while stirring until a gel is formed, and vacuum drying to obtain a xerogel;
[0011] (d) sintering the dry gel for the first time, grinding it after the first sintering and sintering it for the second time to obtain an anion-cation inter-doped carbon-coated positive electrode material.
[0012] Furthermore, the molar ratio of the surfactant, the chelating agent, and the metal ion in the metal ion complexing solution is (0.025-0.04): (0.5-1.5): (2-4).
[0013] Furthermore, the stirring and mixing processes in step (a) and step (b) are both carried out at 60-80°C.
[0014] Furthermore, in the step (c), the mixed solution is heated to 120-140°C.
[0015] Furthermore, in the step (d), the first sintering is performed at 250-350° C. in an inert atmosphere for 3-4 hours, and the second sintering is performed at 500-600° C. in an inert atmosphere for 10-14 hours.
[0016] Furthermore, the sodium source includes one or more of sodium sulfate, sodium nitrate, sodium chloride, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and organic acid salts of sodium.
[0017] Furthermore, the iron source includes one or more of iron powder, ferric phosphate, ferrous oxalate, ferrous acetate, and ferric nitrate.
[0018] Furthermore, the manganese source includes one or more of manganese chloride, manganese nitrate, manganese carbonate, manganese sulfate, manganese oxalate, and manganese dioxide.
[0019] Furthermore, the nickel source includes one or more of nickel chloride, nickel nitrate, nickel carbonate, nickel sulfate, and nickel hydroxide.
[0020] Furthermore, the silicon source includes one or more of tetraethyl orthosilicate, tetraethoxysilane, diethoxymethylsilane, and hexachlorodisilane.
[0021] Furthermore, the fluorine source includes one or both of sodium fluoride and sodium monofluorophosphate.
[0022] Furthermore, the phosphorus source includes one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, and ammonium phosphate.
[0023] Furthermore, the carbon source includes one or more of acetylene black, glucose, sucrose, caramel, starch, CNTs (carbon nanotubes), graphene, graphene oxide, carbon quantum dots, dextrin, and polyvinyl alcohol.
[0024] In a third aspect, the present invention proposes a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is obtained by coating a positive electrode slurry on a positive electrode collector and then drying and rolling it, and the positive electrode slurry comprises the anion- and cation-doped carbon-coated positive electrode material proposed in the first aspect above or the anion- and cation-doped carbon-coated positive electrode material prepared by the method proposed in the second aspect above.
[0025] In a fourth aspect, the present invention proposes an electrical device comprising the sodium ion battery proposed in the third aspect.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] The present invention introduces Mn into the carbon-coated sodium iron pyrophosphate positive electrode material. 2+ 、Ni 2+ Cation and (SiO4F) 5- Anions improve the electronic conductivity, ionic conductivity and structural stability of the sodium iron pyrophosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0029] Figure 1The present invention is a flow chart of the preparation method of the anion-cation inter-doped carbon-coated positive electrode material;
[0030] Figure 2 This is a SEM electron microscope image of the positive electrode material prepared in Example 1 of the present invention;
[0031] Figure 3 XRD diagrams of the positive electrode materials prepared in Example 1 and Comparative Example 3 of the present invention;
[0032] Figure 4 This is a graph of positive electrode discharge gram capacity at different rates for batteries prepared using the positive electrode materials prepared in Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0033] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0034] The following describes the anion-cation inter-doped carbon-coated positive electrode material and its preparation method, sodium ion battery and electrical equipment proposed in the present invention in conjunction with the accompanying drawings.
[0035] The chemical formula of the anion-cation inter-doped carbon-coated cathode material is Na 4+2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z / C, which is Na 4+2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z and C composite material, wherein 0<x≤0.5, 0<y≤0.5, 0<z≤0.3, the mass proportion of C in the positive electrode material is 1% to 3%, the thickness of the carbon coating layer is 1 to 10 nm, and the median particle size Dv50 of the composite material is 2 to 6 μm.
[0036] The present invention introduces Mn into the carbon-coated sodium iron pyrophosphate positive electrode material. 2+ 、Ni 2+ Cation and (SiO4F) 5- Anions greatly improve the electronic conductivity, ionic conductivity and structural stability of the sodium iron pyrophosphate positive electrode material.
[0037] Mn 2+、Ni 2+ with Fe 2+ Having similar ionic radii In the lattice structure, it is easy to Fe 2+ For sodium iron pyrophosphate (NFPP) crystals, Fe 3+ The strong electrostatic repulsion between Fe and O causes Fe to occupy the site of Na, resulting in structural instability and disorder. At the same time, the distortion of Fe-O octahedron causes Na + The diffusion channel of Mn is narrowed. 2+ 、Ni 2+ Cationic doping can interact with Fe elements, effectively inhibiting and regulating Fe in the process of material charge and discharge. 3+ Electrostatic repulsion stabilizes Na + The diffusion channel of Mn improves the ionic conductivity of the material. Single doping with Mn is prone to Jahn-Teller effect, which accelerates the deactivation of the material. Ni doping can inhibit the Jahn-Teller effect of Mn, change the electronic structure of the material, promote the migration of electrons in the material, and improve the electronic conductivity of the material.
[0038] (SiO4F) 5- Anions replace some inactive (PO4) 3- , to form fluorosilicate doping on sodium iron pyrophosphate. 5- The introduction of expanded ion diffusion channels provides rapid Na + The transmission path improves the electrochemical performance, while the diamond-like Fe-Si framework enhances the structural stability of the material; the highly electronegative F - Can combine Ni 2+ Further alleviate the Jahn-Teller effect of Mn, improve material stability, and reduce structural phase change and volume expansion during battery charging and discharging; (SiO4F) 5- Reduces the polyanion group (PO4) 3- Interaction with surrounding electrons improves the conductivity of the material.
[0039] like Figure 1 As shown, the preparation method of the anion-cation inter-doped carbon-coated positive electrode material comprises the following steps:
[0040] (a) weighing a sodium source, an iron source, a manganese source, and a nickel source in molar ratio, dissolving them in water, adding a surfactant and a chelating agent, and stirring and mixing them to obtain a metal ion complex solution;
[0041] (b) weighing a carbon source, a phosphorus source, a silicon source, and a fluorine source in molar ratio, dissolving them in water, adding a metal ion complexing solution, and stirring and mixing to obtain a mixed solution;
[0042] (c) heating the mixed solution to a high temperature, adding an auxiliary agent dropwise while stirring until a gel is formed, and vacuum drying to obtain a xerogel;
[0043] (d) The dry gel is subjected to a first sintering, and after the first sintering, it is ground and subjected to a second sintering to obtain an anion-cation inter-doped carbon-coated positive electrode material.
[0044] In step (a), the molar ratio of the sodium source, the iron source, the manganese source, and the nickel source is determined according to the Na 4+2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z / C is determined. The corresponding metal ion source is weighed according to the molar ratio, and after the ionic metal source is dissolved in water, a surfactant and a chelating agent are added, and stirred at 60-80°C for 1-2 hours until the mixture is evenly mixed to form a metal ion complex solution. In some embodiments, the surfactant is CTAB (hexadecyltrimethylammonium bromide) and the chelating agent is citric acid. In some embodiments, the molar ratio of the surfactant, the chelating agent, and the metal ion in the metal ion complex solution is (0.025-0.04): (0.5-1.5): (2-4). It is understandable that a temperature environment of 60-80°C can be achieved using a water bath.
[0045] The sodium source includes one or more of sodium sulfate, sodium nitrate, sodium chloride, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and organic acid salts of sodium. The iron source includes one or more of iron powder, ferric phosphate, ferrous oxalate, ferrous acetate, and ferric nitrate. The manganese source includes one or more of manganese chloride, manganese nitrate, manganese carbonate, manganese sulfate, manganese oxalate, and manganese dioxide. The nickel source includes one or more of nickel chloride, nickel nitrate, nickel carbonate, nickel sulfate, and nickel hydroxide. It is understood that in the specific implementation process, a suitable metal ion source is selected as needed.
[0046] In step (b), the molar ratio of the carbon source, phosphorus source, silicon source and fluorine source is determined according to the Na 4+2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z / C. Weigh the carbon source, phosphorus source, silicon source and fluorine source according to the molar ratio and dissolve them in water, then add the metal ion complex solution prepared in step (a), and stir at 60-80°C for 2-3h to obtain a mixed solution. It is understood that the temperature environment of 60-80°C can be achieved by using a water bath.
[0047] The silicon source includes one or more of tetraethyl orthosilicate, tetraethoxysilane, diethoxymethylsilane, and hexachlorodisilane. The fluorine source includes one or two of sodium fluoride and sodium monofluorophosphate. The phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and ammonium phosphate. The carbon source includes one or more of acetylene black, glucose, sucrose, caramel, starch, CNTs, graphene, graphene oxide, carbon quantum dots, dextrin, and polyvinyl alcohol. It is understood that in the specific implementation process, suitable raw materials are selected according to needs.
[0048] In step (c), the mixed solution is heated to 120-140° C., and then the auxiliary agent ethylene glycol is added dropwise while stirring until a gel is formed, and then vacuum dried at 80-100° C. for 10-12 hours to obtain a dry gel.
[0049] In step (d), the dry gel is sintered twice, and both sintering processes are carried out under 3% to 5% H2 and 95% to 97% inert atmosphere. The first sintering is at 250 to 350°C for 3 to 4 hours. After the first sintering is completed, the sintered product is taken out and ground and then sintered for the second time. The second sintering is sintered at 500 to 600°C for 10 to 14 hours. After the second sintering is completed, it is cooled in the furnace to obtain an anion-cation inter-doped carbon-coated positive electrode material.
[0050] The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet is obtained by coating a positive electrode slurry on a positive electrode collector and then drying and rolling. The positive electrode slurry comprises the anion-cation inter-doped carbon-coated positive electrode material of the present invention.
[0051] The negative electrode active material used in the preparation process of the negative electrode plate includes at least one of graphene, graphene oxide, soft carbon, hard carbon, expanded graphite, silicon, and mesophase carbon microbeads, preferably hard carbon.
[0052] The present invention is described below in conjunction with specific examples. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0053] Example 1
[0054] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Ni 0.3 Fe 2.4 Mn 0.3 (PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 2%, and the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3.
[0055] The specific steps are as follows:
[0056] S1: Sodium nitrate, iron nitrate, manganese nitrate and nickel nitrate are weighed and dissolved in water according to the molar ratio shown in the above chemical formula, and hexadecyltrimethylammonium bromide (CTAB) and citric acid are added, and stirred at 60° C. for 1 h to obtain a uniformly mixed metal ion complex solution A;
[0057] S2: Glucose, ammonium dihydrogen phosphate, tetraethyl orthosilicate and sodium fluoride were weighed and dissolved in water according to the molar ratio, and the metal ion complex solution A was added, and the mixture was stirred at 80°C for 2 hours to obtain a mixed solution B;
[0058] S3: heating the mixed solution B to 120°C, adding ethylene glycol dropwise while stirring until a gel is formed, and then vacuum drying at 80°C for 10 h to obtain a dry gel C;
[0059] S4: In an atmosphere of 5% H2 and 95% Ar, the dry gel C was sintered at 300°C for 3.5 hours, the sintered product was taken out and ground, and then further sintered at 550°C for 12 hours in an atmosphere of 5% H2 and 95% Ar, and cooled in the furnace to obtain an anion-cation interdoped carbon-coated positive electrode material.
[0060] Example 2
[0061] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.4 Ni 0.3 Fe 2.4 Mn 0.3 (PO4) 1.8 P2O7(SiO4F) 0.2 / C, the mass proportion of C in the positive electrode material is 1%, and the molar ratio of CATB, citric acid and metal ions satisfies 0.025:0.5:2.
[0062] The specific steps are as follows:
[0063] S1: Sodium nitrate, iron nitrate, manganese nitrate and nickel nitrate are weighed and dissolved in water according to the molar ratio shown in the above chemical formula, and hexadecyltrimethylammonium bromide (CTAB) and citric acid are added, and stirred at 70° C. for 2 h to obtain a uniformly mixed metal ion complex solution A;
[0064] S2: Glucose, ammonium dihydrogen phosphate, tetraethyl orthosilicate and sodium fluoride were weighed and dissolved in water according to the molar ratio, and the metal ion complex solution A was added, and the mixture was stirred at 80°C for 2 hours to obtain a mixed solution B;
[0065] S3: heating the mixed solution B to 130°C, adding ethylene glycol dropwise while stirring until a gel is formed, and then vacuum drying at 80°C for 10 h to obtain a dry gel C;
[0066] S4: In an atmosphere of 5% H2 and 95% Ar, the dry gel C was sintered at 250°C for 4 hours, the sintered product was taken out and ground, and then further sintered at 600°C for 10 hours in an atmosphere of 5% H2 and 95% Ar, and cooled in the furnace to obtain an anion- and cation-doped carbon-coated positive electrode material.
[0067] Example 3
[0068] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.1 Ni 0.3 Fe 2.4 Mn 0.3 (PO4) 1.95 P2O7(SiO4F) 0.05 / C, the mass proportion of C in the positive electrode material is 3%, and the molar ratio of CATB, citric acid and metal ions satisfies 0.04:1.5:4.
[0069] The specific steps are as follows:
[0070] S1: Sodium nitrate, iron nitrate, manganese nitrate and nickel nitrate are weighed and dissolved in water according to the molar ratio shown in the above chemical formula, and hexadecyltrimethylammonium bromide (CTAB) and citric acid are added, and stirred at 80° C. for 1 h to obtain a uniformly mixed metal ion complex solution A;
[0071] S2: Glucose, ammonium dihydrogen phosphate, tetraethyl orthosilicate and sodium fluoride were weighed and dissolved in water according to the molar ratio, and the metal ion complex solution A was added, and the mixture was stirred at 80°C for 2 hours to obtain a mixed solution B;
[0072] S3: heating the mixed solution B to 120°C, adding ethylene glycol dropwise while stirring until a gel is formed, and then vacuum drying at 100°C for 10 h to obtain a dry gel C;
[0073] S4: In an atmosphere of 3% H2 and 97% Ar, the dry gel C was sintered at 300°C for 3.5 hours, the sintered product was taken out and ground, and then further sintered at 3% H2 and 97% Ar at 550°C for 12 hours, and cooled in the furnace to obtain an anion-cation interdoped carbon-coated positive electrode material.
[0074] Example 4
[0075] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Ni 0.5 Fe2Mn 0.5 (PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 2%, and the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3.
[0076] The specific steps are as follows:
[0077] S1: Sodium nitrate, iron nitrate, manganese nitrate and nickel nitrate are weighed and dissolved in water according to the molar ratio shown in the above chemical formula, and hexadecyltrimethylammonium bromide (CTAB) and citric acid are added, and stirred at 60° C. for 1 h to obtain a uniformly mixed metal ion complex solution A;
[0078] S2: Glucose, ammonium dihydrogen phosphate, tetraethyl orthosilicate and sodium fluoride were weighed and dissolved in water according to the molar ratio, and the metal ion complex solution A was added, and the mixture was stirred at 70°C for 3 hours to obtain a mixed solution B;
[0079] S3: heating the mixed solution B to 140°C, adding ethylene glycol dropwise while stirring until a gel is formed, and then vacuum drying at 80°C for 10 h to obtain a dry gel C;
[0080] S4: In an atmosphere of 5% H2 and 95% Ar, the dry gel C was sintered at 300°C for 3.5 hours, the sintered product was taken out and ground, and then further sintered at 550°C for 12 hours in an atmosphere of 5% H2 and 95% Ar, and cooled in the furnace to obtain an anion-cation interdoped carbon-coated positive electrode material.
[0081] Example 5
[0082] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Ni 0.1 Fe 2.8 Mn 0.1 (PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 2%, and the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3.
[0083] The specific steps are as follows:
[0084] S1: Sodium nitrate, iron nitrate, manganese nitrate and nickel nitrate are weighed and dissolved in water according to the molar ratio shown in the above chemical formula, and hexadecyltrimethylammonium bromide (CTAB) and citric acid are added, and stirred at 60° C. for 1 h to obtain a uniformly mixed metal ion complex solution A;
[0085] S2: Glucose, ammonium dihydrogen phosphate, tetraethyl orthosilicate and sodium fluoride were weighed and dissolved in water according to the molar ratio, and the metal ion complex solution A was added, and the mixture was stirred at 80°C for 2 hours to obtain a mixed solution B;
[0086] S3: heating the mixed solution B to 120°C, adding ethylene glycol dropwise while stirring until a gel is formed, and then vacuum drying at 80°C for 10 h to obtain a dry gel C;
[0087] S4: In an atmosphere of 5% H2 and 95% Ar, the dry gel C was sintered at 300°C for 3.5 hours, the sintered product was taken out and ground, and then further sintered at 550°C for 12 hours in an atmosphere of 5% H2 and 95% Ar, and cooled in the furnace to obtain an anion-cation interdoped carbon-coated positive electrode material.
[0088] Comparative Example 1
[0089] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na4Ni 0.3 Fe 2.4 Mn 0.3 (PO4)2P2O7 / C, the mass proportion of C in the positive electrode material is 2%, the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3, and other conditions are the same as those in Example 1.
[0090] Comparative Example 2
[0091] The molar ratio of sodium source, iron source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Fe3(PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 2%, the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3, and other conditions are the same as those in Example 1.
[0092] Comparative Example 3
[0093] The molar ratio of the sodium source, iron source and phosphorus source satisfies Na4Fe3(PO4)2P2O7 / C, the mass proportion of C in the positive electrode material is 2%, the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3, and other conditions are the same as in Example 1.
[0094] Comparative Example 4
[0095] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Ni 0.3 Fe 2.4 Mn 0.3 (PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 4%, the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3, and other conditions are the same as those in Example 1.
[0096] Comparative Example 5
[0097] The molar ratio of sodium source, iron source, manganese source, nickel source, phosphorus source, silicon source and fluorine source satisfies Na 4.2 Ni 0.3 Fe 2.4 Mn 0.3 (PO4) 1.9 P2O7(SiO4F) 0.1 / C, the mass proportion of C in the positive electrode material is 0.1%, the molar ratio of CATB, citric acid and metal ions satisfies 0.03:1:3, and other conditions are the same as those in Example 1.
[0098] Test Example 1
[0099] The positive electrode material prepared in Example 1 was tested by field emission scanning electron microscope (SEM). The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the positive electrode material prepared in Example 1 has a regular shape and good morphology.
[0100] Test Example 2
[0101] XRD test was performed on the positive electrode materials prepared in Example 1 and Comparative Example 3. The test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the characteristic peak positions of the positive electrode materials of Example 1 and Comparative Example 3 are consistent, and the positive electrode material prepared in Example 1 has no impurity peaks, which shows that anion and cation doping do not affect the structure of the material.
[0102] Test Example 3
[0103] The positive electrode sheets, buckle batteries and soft-pack batteries prepared using the positive electrode materials of Examples 1 to 5 and Comparative Examples 1 to 4 were respectively subjected to positive electrode sheet resistance test, buckle rate stability test, soft-pack DC internal resistance test and soft-pack cycle number test. The test results are shown in Table 1 below.
[0104] The positive electrode sheet is prepared by: adding solvent N-methylpyrrolidone (NMP) to adjust the solid content to 60%±1% according to the mass ratio of positive electrode material: conductive agent conductive carbon black (SP): binder polyvinylidene fluoride (PVDF) = 95:2.5:2.5 to obtain positive electrode slurry. The positive electrode slurry is evenly coated on the aluminum foil, and the single-sided coating surface density is 150g / m 2 After baking and rolling, the positive electrode sheet is obtained. The thickness of the aluminum foil is 14μm and the compaction density is 2.0g / cm 3 .
[0105] The preparation method of the button battery is as follows: in a glove box, the positive electrode plate, the separator and the electrolyte, and the counter electrode (sodium plate) are assembled in sequence to obtain a CR2032 button battery.
[0106] The preparation method of soft-pack batteries is as follows: stack the positive electrode sheet, hard carbon negative electrode sheet and polyethylene separator, assemble and bake until the moisture content is qualified, inject electrolyte, hot press and high-temperature standing, then package, divide the volume and stand at room temperature to obtain a soft-pack 505060 finished battery, among which the polyethylene separator is PE+OBS separator (polyethylene+solvent-based coating separator).
[0107] The positive electrode sheet resistance is tested by using a sheet resistance meter, model BER2500 (IEST Yuanneng Technology), with an electrode diameter of 14 mm, an applied pressure of 20 MPa, and a duration of 15 s.
[0108] The method for testing the stability of the charge rate is as follows: testing at 25°C on an electrochemical workstation battery testing system, the current density of the charge test is 0.1C, 0.5C, 1C, 5C, 20C, 0.1C, and the charge and discharge voltage window is 1.5V~3.5V.
[0109] The test method of the soft-pack battery discharge DC internal resistance is: test at 25°C on the electrochemical workstation battery test system, adjust the battery capacity to 50% SOC and leave it for 2 hours, record the end-of-stay voltage U1, discharge with current I (2C) for 10 seconds, record the end-of-discharge voltage U2, DCR = (U1-U2) / I.
[0110] The soft-pack battery cycle stability test method is: testing at 45°C on an electrochemical workstation battery testing system, the test charge and discharge current density is 1C / 1C, and the charge and discharge voltage window is 1.5V~3.4V.
[0111] Table 1:
[0112]
[0113]
[0114] According to Table 1, the positive electrode sheet resistance and DCR of Examples 1 to 5 are generally smaller than those of the comparative example, and the discharge performance and cycle performance at high rate are better than those of the comparative example.
[0115] The discharge performance and cycle performance at high rates of Examples 1 to 5 are better than those of Comparative Example 1 because (SiO4F) 5- Anion doping can provide fast Na + transmission path, enhancing the discharge performance of the material at high rates; at the same time, it can improve the structural stability of the material, reduce the structural phase change and volume expansion during the battery charging and discharging process, and improve the cycle performance of the material at high temperatures.
[0116] The discharge performance and cycle performance at high rate of Examples 1 to 5 are better than those of Comparative Example 2 because Mn 2+ Cation doping can increase the specific capacity of the material, Mn 2+ 、Ni 2+ Cations can effectively inhibit and regulate the Fe 3 + Electrostatic repulsion stabilizes Na + diffusion channels, improve the ionic conductivity of the material, enhance the rate performance of the material, reduce polarization, and improve the cycle performance of the material.
[0117] The positive electrode sheet resistance and DCR of Examples 1 to 5 are smaller than those of Comparative Example 3, and the cycle performance is better than that of Comparative Example 3. The reason is that Mn 2+ 、Ni 2+ Cation and (SiO4F) 5- Anion inter-doping structure can utilize Mn 2+ 、Ni 2+ Cations can enhance the electronic and ionic conductivity of materials and utilize (SiO4F) 5- Anions optimize the structural stability of the material, while F and Ni elements can alleviate the 2+ The Jahn-Teller effect and the interaction between anions and cations greatly improve the electronic conductivity, ionic conductivity and structural stability of the material.
[0118] The gram capacity and cycle performance of Examples 1 to 5 are better than those of Comparative Example 4. The reason is that the carbon layer in Comparative Example 4 has too much coating and the coating has no capacity. Although the coating can enhance electron transmission and improve the capacity of the material, too much coating will lead to a decrease in the capacity itself. Secondly, too much carbon coating causes the carbon layer to develop from a flat and orderly state to a disordered state, increasing the surface area of the material. The disordered structure will extend the transmission distance of sodium ions, increase side reactions during the cycle, and reduce performance.
[0119] The gram capacity of Examples 1 to 5 is higher than that of Comparative Example 5, and the rate performance and cycle performance are better than those of Comparative Example 5. The reason is that the carbon coating amount of Comparative Example 5 is too small, and an effective electron / ion transmission path cannot be established, and all aspects of the material performance are reduced.
[0120] Test Example 4
[0121] The discharge capacity of the buckle battery prepared by Example 1 and Comparative Example 3 after 10 cycles at different rates was tested. The test method is: testing at 25°C on an electrochemical workstation battery test system, the current density of the buckle test is 0.1C, 0.5C, 1C, 5C, 20C, 0.1C, and the charge and discharge voltage window is 1.5V to 3.5V. The test results are as follows: Figure 4 As shown. Figure 4 It can be seen that the discharge performance of Example 1 at different rates is better than that of Example 3.
[0122] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0123] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0124] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A carbon-coated positive electrode material doped with anions and cations, characterized in that: The positive electrode material is Na 4+ 2z Ni x Fe 3-x-y Mn y (PO4) 2-z P2O7(SiO4F) z and C composite material, wherein 0<x≤0.5, 0<y≤0.5, 0<z≤0.3, and the mass proportion of C in the positive electrode material is 1% to 3%.
2. A method for preparing an anion-cation co-doped carbon-coated positive electrode material, characterized in that: The method for preparing the positive electrode material according to claim 1 comprises the following steps: (a) weighing a sodium source, an iron source, a manganese source, and a nickel source in molar ratio, dissolving them in water, adding a surfactant and a chelating agent, and stirring and mixing them to obtain a metal ion complex solution; (b) weighing a carbon source, a phosphorus source, a silicon source, and a fluorine source in molar ratio and dissolving them in water, adding the metal ion complex solution, and stirring and mixing to obtain a mixed solution; (c) heating the mixed solution to a high temperature, adding an auxiliary agent dropwise while stirring until a gel is formed, and vacuum drying to obtain a xerogel; (d) sintering the dry gel for the first time, grinding it after the first sintering and sintering it for the second time to obtain an anion-cation inter-doped carbon-coated positive electrode material.
3. The method according to claim 2, characterized in that The molar ratio of the surfactant, the chelating agent and the metal ion in the metal ion complexing solution is (0.025-0.04): (0.5-1.5): (2-4).
4. The method according to claim 2, characterized in that The stirring and mixing processes in step (a) and step (b) are both carried out at 60-80°C.
5. The method according to claim 2, characterized in that In the step (c), the mixed solution is heated to 120-140°C.
6. The method according to claim 2, characterized in that In the step (d), the first sintering is performed at 250-350° C. in an inert atmosphere for 3-4 hours, and the second sintering is performed at 500-600° C. in an inert atmosphere for 10-14 hours.
7. The method according to claim 2, characterized in that The sodium source includes one or more of sodium sulfate, sodium nitrate, sodium chloride, sodium carbonate, sodium bicarbonate, sodium fluoride, sodium dihydrogen phosphate, and organic acid salts of sodium; And / or, the iron source includes one or more of iron powder, ferric phosphate, ferrous oxalate, ferrous acetate, and ferric nitrate; And / or, the manganese source includes one or more of manganese chloride, manganese nitrate, manganese carbonate, manganese sulfate, manganese oxalate, and manganese dioxide; And / or, the nickel source includes one or more of nickel chloride, nickel nitrate, nickel carbonate, nickel sulfate, and nickel hydroxide.
8. The method according to claim 2, characterized in that The silicon source includes one or more of tetraethyl orthosilicate, tetraethoxysilane, diethoxymethylsilane, and hexachlorodisilane; And / or, the fluorine source includes one or both of sodium fluoride and sodium monofluorophosphate; and / or, the phosphorus source comprises one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, and ammonium phosphate; And / or, the carbon source includes one or more of acetylene black, glucose, sucrose, caramel, starch, CNTs, graphene, graphene oxide, carbon quantum dots, dextrin, and polyvinyl alcohol.
9. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet is obtained by coating a positive electrode slurry on a positive electrode collector, drying and rolling the resulting slurry. The positive electrode slurry comprises the anion-cation inter-doped carbon-coated positive electrode material according to claim 1 or the anion-cation inter-doped carbon-coated positive electrode material prepared by the methods according to claims 2 to 8.
10. An electrical device, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material prepared by gel method and preparation method of sodium-ion battery positive electrode material
CN114873575A
Carbon-coated sodium-rich sodium ferric pyrophosphate composite positive electrode material, preparation method and application
CN116169264A
Iron-manganese-cobalt-based sodium-rich anion doped positive electrode material and preparation method thereof
CN117012956A
Iron-based polyphosphate material with uniform mesoporous structure as well as preparation and application of iron-based polyphosphate material
CN118561258A
Positive electrode material, preparation method thereof and sodium ion battery
CN119029171A
Cited By
Fluorophosphoric acid and sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof
CN121149174A